ELEKTRON TÁLIM ORTALÍǴÍNDA INFORMATIKA KURSÍN OQÍTÍWDÍŃ ÚZLIKSIZ SISTEMASÍ HÁM ONÍŃ MAZMUNÍ - Kenesbayev, A. (SCIENCE and SOCIETY, 2024)
This article talks about the use and creation of electronic resources in the continuous system of teaching the computer science course. The article mainly deals with the digitalization of education and its importance in education.